Prototype of Electrical Power Breaker Automation ON PHB-TR Using Microcontroller-Based IOT For Flood-Prone Areas - Kusuma Wardhany, Arum; Setya, Hilman Luthfi; Kamil, Ikhsan; Efendi, Erwan Tri (Eksergi, 2025)
The flood disaster caused losses for PT PLN consumers whose areas were flooded. To prevent electric shock accidents due to flooding, PT PLN took steps to extinguish distribution substations whose areas were affected by flooding. This step was taken to maintain the safety of the flood-affected community from being electrocuted, but this resulted in a loss for PT PLN, namely the selling kWh that was not distributed. In this study, the method used is research and development, where the author makes an idea to overcome the problem of the length of power outage due to flooding by making a PHB-TR Control Prototype for Distribution Substations. Where this prototype is an innovation to replace the main switch on the PHB-TR with MCCB and MCB which are applied in the box panel. With this prototype, PT PLN officers can speed up the process of blackout areas experiencing flooding quickly by controlling the MCCB and MCB at the PHB-TR distribution substation from the PLN office, but still maintaining the reliability of the 20 kV Medium Voltage Network. This prototype is based on the Internet of Things that can be controlled remotely using the Blynk application that can be operated from smartphones and computers. This prototype design is expected to help PLN officers to cut off the PHB-TR load from the PLN office or remotely, as well as some of the benefits that PT PLN can receive from this tool innovation, namely saving kWh that is not channeled and a positive image for PT PLN will be maintained by maintain the reliability of the electrical distribution system.